Nanoscale stimulation of osteoblastogenesis from mesenchymal stem cells: nanotopography and nanokicking. (March 2015) - Pemberton, Gabriel D; Childs, Peter; Reid, Stuart; Nikukar, Habib; Tsimbouri, P Monica; Gadegaard, Nikolaj; Curtis, Adam SG; Dalby, Matthew J
Aim: Mesenchymal stem cells (MSCs) have large regenerative potential to replace damaged cells from several tissues along the mesodermal lineage. The potency of these cells promises to change the longer term prognosis for many degenerative conditions currently suffered by our aging population. We have endeavored to demonstrate our ability to induce osteoblatogenesis in MSCs using high-frequency (1000–5000 Hz) piezo-driven nanodisplacements (16–30 nm displacements) in a vertical direction.Materials & methods: Osteoblastogenesis has been determined by the upregulation of osteoblasic genes such as osteonectin ( ONN ), RUNX2 and Osterix, assessed via quantitative real-time PCR; the increase of osteocalcin (OCN) and osteopontin (OPN) at the protein level and the deposition of calcium phosphate determined by histological staining.Results: Intriguingly, we have observed a relationship between nanotopography and piezo-stimulated mechanotransduction and possibly see evidence of two differing osteogenic mechanisms at work. These data provide confidence in nanomechanotransduction for stem cell differentiation without dependence on soluble factors and complex chemistries.Conclusion: In the future it is envisaged that this technology may have beneficial therapeutic applications in the healthcare industry, for conditions whose overall phenotype maybe characterized by weak or damaged bones (e.g., osteoporosis and bone fractures), and which can benefit from having an increased number of osteoblastic cells in vivo .